Adaptation of a microbial community to demand-oriented biological methanation - Khesali Aghtaei, Hoda; Püttker, Sebastian; Maus, Irena; Heyer, Robert; Huang, Liren; Sczyrba, Alexander; Reichl, Udo; Benndorf, Dirk (Biotechnology for biofuels and bioproducts, 2022)
Background Biological conversion of the surplus of renewable electricity and carbon dioxide (CO 2 ) from biogas plants to biomethane (CH 4 ) could support energy storage and strengthen the power grid. Biological methanation (BM) is linked closely to the activity of biogas-producing Bacteria and methanogenic Archaea . During reactor operations, the microbiome is often subject to various changes, e.g., substrate limitation or pH-shifts, whereby the microorganisms are challenged to adapt to the new conditions. In this study, various process parameters including pH value, CH 4 production rate, conversion yields and final gas composition were monitored for a hydrogenotrophic-adapted microbial community cultivated in a laboratory-scale BM reactor. To investigate the robustness of the BM process regarding power oscillations, the biogas microbiome was exposed to five hydrogen (H 2 )-feeding regimes lasting several days. Results Applying various “on–off” H 2 -feeding regimes, the CH 4 production rate recovered quickly, demonstrating a significant resilience of the microbial community. Analyses of the taxonomic composition of the microbiome revealed a high abundance of the bacterial phyla Firmicutes , Bacteroidota and Thermotogota followed by hydrogenotrophic Archaea of the phylum Methanobacteriota . Homo-acetogenic and heterotrophic fermenting Bacteria formed a complex food web with methanogens. The abundance of the methanogenic Archaea roughly doubled during discontinuous H 2 -feeding, which was related mainly to an increase in acetoclastic Methanothrix species. Results also suggested that Bacteria feeding on methanogens could reduce overall CH 4 production. On the other hand, using inactive biomass as a substrate could support the growth of methanogenic Archaea . During the BM process, the additional production of H 2 by fermenting Bacteria seemed to support the maintenance of hydrogenotrophic methanogens at non-H 2 -feeding phases. Besides the elusive role of Methanothrix during the H 2 -feeding phases, acetate consumption and pH maintenance at the non-feeding phase can be assigned to this species. Conclusions Taken together, the high adaptive potential of microbial communities contributes to the robustness of BM processes during discontinuous H 2 -feeding and supports the commercial use of BM processes for energy storage. Discontinuous feeding strategies could be used to enrich methanogenic Archaea during the establishment of a microbial community for BM. Both findings could contribute to design and improve BM processes from lab to pilot scale.